Biochemical changes in trace elements in antral follicles of goat - Sharma, R K; Vats, R (The Indian Journal of Animal Sciences, 2012)
Biochemical analysis of 6 categories of normal developing antral follicles of goat (Capra hircus) was conducted to study the sequential pattern of changes in trace elements. Fe increased from 43.67 in category 1 to 54.59 Âµg/g in category 5 follicles. The variations in Cu and Mn did not reveal any specific trend but maxima for Mn was observed in medium antral follicles and for Cu in large antral follicles. These biochemical variations in trace elements have been discussed in relation to the physiology of the follicles.